2008
DOI: 10.1136/gut.2008.154120
|View full text |Cite
|
Sign up to set email alerts
|

The systemic inflammatory response syndrome is predictive of renal dysfunction in patients with non-paracetamol-induced acute liver failure

Abstract: SIRS is strongly associated with the development of renal dysfunction in patients with non-paracetamol-induced ALF. It is proposed that the systemic inflammatory cascade plays a key role in its pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
76
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 123 publications
(79 citation statements)
references
References 58 publications
3
76
0
Order By: Relevance
“…Our findings are consistent with other reports investigating the frequency of renal dysfunction in ALF [17][18][19][20][21] . The prevalence of renal dysfunction in patients with ALF has been previous reported to be 38% to 79% [17][18][19][20][21] .…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our findings are consistent with other reports investigating the frequency of renal dysfunction in ALF [17][18][19][20][21] . The prevalence of renal dysfunction in patients with ALF has been previous reported to be 38% to 79% [17][18][19][20][21] .…”
Section: Discussionsupporting
confidence: 93%
“…Differences in prevalence are likely due to variable definitions used to identify renal dysfunction and differences in the population studied. Prior studies have reported association of renal dysfunction with increased mortality in ALF patients 17,19,20 , our data expand prior experience and emphasize that mortality in patients with renal dysfunction and ALF is high and that mortality increases with severity of renal dysfunction even after controlling for etiology of ALF, INR, total bilirubin and region. Our study evaluated the severity of renal dysfunction not only in APAP-induced ALF but also in several etiologies of ALF and its impact on mortality using a multivariate analysis.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations